Associations between serum total bilirubin and overactive bladder from the National Health and Nutrition Examination Survey - Jiang, Bo; Ling, Cunbao; Dong, Binbin; Lu, Xiaoming; Liu, Yadong (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between serum total bilirubin (STB) concentrations and the risk of overactive bladder (OAB) remains uncertain. This study aims to explore the potential connection between STB and OAB.MethodWe utilized data from the National Health and Nutrition Examination Survey (NHANES) database for the years 2001-2020. Weighted multivariate logistic regression and restricted cubic spline (RCS) analysis assessed the relationship between STB and OAB. Interaction analyses on subgroups were performed to validate the findings.ResultsThe study included 28,958 participants, with 5,313 identified as having OAB. The results from the fully adjusted models revealed an odds ratio (OR) of 0.98 (95% CI: 0.97, 0.99) and a statistically significant P value of less than 0.001 for the relationship between STB and OAB. Notably, individuals in the second and third tertiles exhibited significant differences compared to those in the lowest STB tertile, with respective odds ratios (P values) of 0.88 (0.04) and 0.80 (<0.001). RCS analysis indicated a non-linear association between STB and OAB (P for nonlinearity = 0.042), with an inflection point at 16.8 μmol/L. The association between STB and OAB exhibited consistency across various subgroups, except for stratification by age and diabetes status(P for interaction = 0.002 and 0.004, respectively), indicating a stronger correlation in individuals younger than 60 years or those without diabetes.ConclusionThese findings suggest an inverse association between STB concentrations below 16.8 μmol/L and the incidence of OAB. Bilirubin could potentially serve as an intervention or risk assessment tool for OAB in future studies.